2000
DOI: 10.1111/j.1540-8159.2000.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Transmural Linear Ablation

Abstract: The purpose of this study is to describe the characteristics of lesions created using radiofrequency (RF) energy delivered through a saline/foam electrode that is designed to simplify ablation of the isthmus between the tricuspid annulus (TA) and the inferior vena cava (IVC). We compared the changes in the electrophysiological parameters produced by the ablation to histological findings. In search of a more practical and effective atrial flutter ablation method, various energy modifications and catheter design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Electrogram amplitude reduction and pacing threshold increase have been described as means to evaluate effective lesion creation. 15,16) The present results also demonstrated that a lower atrial pacing threshold before ablation (0.5-2.0 V) correlates with higher atrial electrogram amplitudes and greater reduction of atrial electrogram amplitude by ablation, and a larger atrial pacing threshold ratio (> 4, postablation/preablation) correlates with greater reduction of atrial electrogram amplitudes and greater reduction of the atrial electrogram ratio (postablation/preablation) after ablation. However, their predictive accuracy was low regarding continuous and transmural lesion formation in our study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Electrogram amplitude reduction and pacing threshold increase have been described as means to evaluate effective lesion creation. 15,16) The present results also demonstrated that a lower atrial pacing threshold before ablation (0.5-2.0 V) correlates with higher atrial electrogram amplitudes and greater reduction of atrial electrogram amplitude by ablation, and a larger atrial pacing threshold ratio (> 4, postablation/preablation) correlates with greater reduction of atrial electrogram amplitudes and greater reduction of the atrial electrogram ratio (postablation/preablation) after ablation. However, their predictive accuracy was low regarding continuous and transmural lesion formation in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Liem, et al produced transmural lesions across the cavo-tricuspid isthmus in all 7 of their sheep by this technique. 15) Their results may be explained by the shorter distance, smooth surface, and easy positioning of the catheter at the cavo-tricuspid isthmus. We achieved a higher success rate (75%) for cavo-tricuspid isthmus ablation than for other lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although such an outcome might be expected, it may not be true in a broader sense. For example, lesions created by radio-frequency ablation can decrease pacing thresholds (26). The standard deviation for the data (Table 1) does not allow us to conclude whether one of the thresholds is affected more than the other.…”
Section: Discussionmentioning
confidence: 88%
“…35 It is suggested that cavotricuspid isthmus ablation may create a transmural lesion as described by Bing Liem. 36 From these findings, it is suggested that linear ablation of the cavotricuspid isthmus may influence the vagal fibers innervating the sinus node, and may change heart rate and heart rate variability if the vagal nerve fibers to the sinus node are distributed near the isthmus. From the findings of the present study, it is concluded that vagal nerve fibers destined for the sinus node are distributed sparsely in the isthmus.…”
Section: Autonomic Nerve Innervation Of Sinus Node and Atrioventriculmentioning
confidence: 99%
“…Although linear ablation from the endocardium of the cavotricuspid isthmus can create a transmural lesion in canine heart, [34][35][36] it is not possible for this lesion to extend into the fat pad, which is localized on the epicardial surface. 6 However, anatomical and histological investigations were not performed in the present study.…”
Section: Limitations Of the Studymentioning
confidence: 99%